Identification of lobetyolin as a major antimalarial constituent of the roots of Lobelia giberroa Hemsl. (April 2022) - Tadege, Getnet; Alebachew, Yonatan; Hymete, Ariaya; Tadesse, Solomon
Abstract: Lobelia giberroa Hemsl. is an endogenous Ethiopian medicinal plant with a long history of use in the treatment of malaria, bacterial and fungal diseases, and cancer. Here, we present the in vivo bioassay-guided fractionation of the 80% methanol extract of L. giberroa roots, which led to the isolation of lobetyolin. L. giberroa roots were extracted with 80% methanol, and the dried 80% methanol extract was fractionated with hexane, ethyl acetate, methanol, and water. Acute oral toxicity study was conducted according to the Organisation for Economic Co-operation and Development Guideline 425 by using female Swiss albino mice. Antimalarial activity was assessed in Plasmodium berghei -infected Swiss albino mice. Through in vivo bioassay-guided fractionation processes lobetyolin, a C14-polyacetylene glucoside, was isolated from the methanol fraction by silica gel column chromatography as the main active ingredient from the plant. The chemical structure of lobetyolin was elucidated by interpretation of spectroscopic data ( 1 HNMR, 13 CNMR, IR. MS) including two dimensional NMR. The plant extract was considered safe for administration up to 2000 mg/kg. In the four-day suppressive test, the 80% methanol extract (400 mg/kg), methanol fraction (400 mg/kg), and lobetyolin (100 mg/kg) exhibited antimalarial activity, with chemosuppression values of 73.05, 64.37, and 68.21%, respectively. Compared to the negative control, which had a mean survival time of 7 days, the lobetyolin (100 mg/kg) and methanol fraction (400 mg/kg) treated groups had mean survival times of 18 and 19 days, respectively. The current study supports the traditional use of the plant for the treatment of malaria. The structural differences between lobetyolin and existing antimalarials, as well as its previously unknown antimalarial activity, make it of interest as an early lead compound for further chemical optimization. Graphical abstract: Image 1 Highlights: Multi-drug resistant malaria parasites urge the discovery of newer drugs. Lobelia giberroa is an indigenous traditional antimalarial plant of Ethiopia. In vivo antimalarial-activity-guided fractionation led to the isolation of lobetyolin. Lobetyolin exhibits a promising antimalarial activity with an ED50 of 36.8 mg/kg. Lobetyolin is a potential lead compound to develop a new class of antimalarial drugs.